Business Strategy Planning For Makaroni Cakalang - Ransum Si Tante - Runi, Vega; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
Ransum Si Tante is a culinary business that combines the traditional flavors of Manadonese culinary with modern ingredients that is macaroni. Business issues that exist in the company are the sales that have not reached the target, the lack of resources to support the production, and the lack of public awareness in Bandung about its product, which is Cakalang fish. Several analysis are used for exploring business issues to find the root of the problem. The analysis are the external and internal analysis, the EFAS and IFAS method, and SWOT analysis. The roots of the problems are the lack of awareness on Cakalang fish for consumers in Bandung, no outlet and the lack of sales channel for optimal direct selling activities, and the production process is done by only one person. In searching for a solution to the root of the problem, TOWS Matrix formulation and functional strategy are used. TOWS Matrix formulation is a tool that can formulate the best solution in creating business strategies that can be used to solve the problems. Functional strategy is a strategy derived from the TOWS Matrix result that consists of five types of strategies, which are marketing, operational, distribution, human resource, and financial strategy. The implementation plan of Ransum Si Tante should be able to improve management to be better than before. Based on the esternal and internal analysis and weighing of EFAS and IFAS, the strategy that should be executed is Growth strategy. Recommendations for solutions to the root causes are summarized in the new business model where the model is a reference to educate the public about the Cakalang fish through key activities; to increase the number of channel sales and direct selling activities through distribution channel, customer relationship, and new customer segments; and human resource solutions that are needed to make production and promotion processes be more effective through key resources. Keywords: Indonesian Culinary, Ransum Si Tante, Business Strategy